Advanced strategies to enhance the performances of crystallization and precipitation of biopharmaceuticals - Pu, Siyu (Nanyang Technological University, 2023)
This dissertation describes advanced crystallization and precipitation strategies to improve process efficiency and product quality of biopharmaceuticals using bioactive glycopeptide vancomycin hydrochloride (Van) and protein lysozyme (LYZ) as the model biopharmaceuticals. The first study focuses on the phase behavior of salting-out room-temperature crystallization of Van to determine crystallization conditions (i.e., pH, salt and peptide’s concentrations, incubation time) to avoid needle-shaped crystal formation. The second study compared the antisolvent (with organic solvent) and salting-out methods in their precipitation efficiency and product qualities of Van. In the third study, we evaluated for the first time the use of continuous slug flow crystallizer (CSFC) in bulk seeded protein crystallization, using lysozyme (LYZ) as the model protein. Lastly, in the fourth study, we developed a segmented slug flow crystallizer (SFC) of LYZ operated at a short residence time to improve the width of the crystal size distribution (CSD) and CSD’s reproducibility.